2014
DOI: 10.1186/1751-0147-56-25
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic emphysema associated with ultrasound-guided liver biopsy in a dog

Abstract: An eleven-year-old Chinese Crested Powder Puff dog presented with polydipsia/polyuria, inappetence, diarrhea and vomiting underwent an ultrasound-guided percutaneous liver biopsy. Two days post-biopsy the clinical condition of the dog acutely deteriorated with fever, dyspnea, ataxia and subcutaneous emphysema. Radiographs and ultrasound showed focal severe hepatic emphysema in the region of the previous liver biopsy. Post-mortem examination revealed chronic hepatitis with dissecting fibrosis, acute hepatitis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Moreover, a poor outcome was associated with an increase of liver enzymes and liver neoplasia, and both factors were linked to parenchymal emphysema. In fact, parenchymal emphysema was always seen concomitant to liver lesions, such as suppurative hepatitis and neoplasia, which have a poor prognosis per se . Ultrasound was useful for identifying liver abscesses, which are described on ultrasound as poorly echogenic cavitated areas with enhancement artifact .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a poor outcome was associated with an increase of liver enzymes and liver neoplasia, and both factors were linked to parenchymal emphysema. In fact, parenchymal emphysema was always seen concomitant to liver lesions, such as suppurative hepatitis and neoplasia, which have a poor prognosis per se . Ultrasound was useful for identifying liver abscesses, which are described on ultrasound as poorly echogenic cavitated areas with enhancement artifact .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, parenchymal emphysema was always seen concomitant to liver lesions, such as suppurative hepatitis and neoplasia, which have a poor prognosis per se. [3][4][5][6][7] Ultrasound was useful for identifying liver abscesses, which are described on ultrasound as poorly echogenic cavitated areas with enhancement artifact. 2,3 In this study, abscesses containing gas were always multiple and concomitant to other ultrasonographic changes of the parenchyma, indicating diffuse hepatitis.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…The signs of icterus, PU, PD, and dehydration observed in this study have been earlier reported in hepatic disorders [ 1 , 7 ], but these signs have not been specifically documented for liver cirrhosis of dogs. Jaundice and icterus are hallmark of hepatic disorders [ 1 ] and clinically hepatic dysfunction may be manifested by signs of diarrhea, PU, PD and dehydration [ 7 , 8 ]. PU and PD have been attributed to impaired adrenal steroid metabolism, altered portal vein osmoreceptor, loss of renal medullary concentration gradient, and encephalopathy [ 6 ].…”
Section: Discussionmentioning
confidence: 99%